2023
DOI: 10.3390/biology12010106
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Whole-Transcriptome Profiles in Response to Acute Hypersaline Challenge in Chinese Razor Clam Sinonovacula constricta

Abstract: The Chinese razor clam (Sinonovacula constricta) is an important for Chinese aquaculture marine bivalve that naturally occurs across intertidal and estuarine areas subjected to significant changes in salinity level. However, the information on the molecular mechanisms related to high salinity stress in the species remain limited. In this study, nine gill samples of S. constricta treated with 20, 30, and 40 ppt salinity for 24 h were used for whole-transcriptome RNA sequencing, and a regulatory network of compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that salinity stress activated the expression of genes related to amino acid metabolic pathways, such as ATPGD, CSAD, and P5CS, in response to changes in osmotic status and adaption to osmotic stress conditions in the Manila clam Ruditapes philippinarum (Nie et al, 2017). Similarly, in S. constricta, the changes in the expression of these genes at high salinity occur because free amino acids play important roles in regulating osmotic pressure in razor clams (Cao et al, 2023). ACOX1 is an important gene in the development and nutritional regulation of aquatic animals (Morais et al, 2007), which regulates the conversion process between propionyl-COA and acrylyl-COA, thereby affecting the synthesis of Ala (Oaxaca-Castillo et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that salinity stress activated the expression of genes related to amino acid metabolic pathways, such as ATPGD, CSAD, and P5CS, in response to changes in osmotic status and adaption to osmotic stress conditions in the Manila clam Ruditapes philippinarum (Nie et al, 2017). Similarly, in S. constricta, the changes in the expression of these genes at high salinity occur because free amino acids play important roles in regulating osmotic pressure in razor clams (Cao et al, 2023). ACOX1 is an important gene in the development and nutritional regulation of aquatic animals (Morais et al, 2007), which regulates the conversion process between propionyl-COA and acrylyl-COA, thereby affecting the synthesis of Ala (Oaxaca-Castillo et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…ncRNAs can be classified as small nuclear RNAs (snRNAs) or long noncoding RNAs (lncRNAs) based on the quantity of nucleotides they contain. snRNAs can be separated into circular RNAs (circRNAs) and microRNAs (miRNAs) based on distinct production pathways [ 127 ]. Since the discovery of the RNA interference process, researchers have paid increasing attention to the processes of non-coding RNA (ncRNA) regulation [ 128 ].…”
Section: Epigenetic Modification In Diabetic Wound Healingmentioning
confidence: 99%